The Effect of Reciprocal Imitation Training on Social Skills of Children with Autism - Parastou Moghim-Islam; Ma'soumeh Pourmohammadreza-Tajrishi; Hojatollah Haghgou (University of Social Welfare and Rehabilitation Sciences, 2014)
Objective: the present research aimed to determine the effect of reciprocal imitation training on social skills of children with Autism. Materials & Methods: This was a qusi-experimental study with repeated measures. Fourteen 5 to 7 years old children with high function autism (3 girls and 11 boys) were selected in convenience from who were referred to one private clinic at Tehran in 2012-2013. They were assigned randomly to experimental and control groups equally. Children were evaluated by Autism Social Skills Profile (Belini, 2006) 3 times before training sessions and 3 times after them. The experimental group were trained in 20 sessions (twice a week each session lasts for one hour) and received reciprocal imitation. Data were analyzed by multivariate analysis of variance (MANOVA) with repeated measures. Results: The results of MANOVA showed that reciprocal imitation training has increased significantly (p0.05). Conclusion: We can conclude that the reciprocal imitation training leads to improvement of social skills, social interaction and social participation of children with high function autism. It is recommended to use this program in educational and social settings for autistic children. Also, it is suggested as a part of family education programs or planned programs for preschool children with autism.